Pay for tax certainty? Advance tax rulings for risky investment under multi-dimensional tax uncertainty - An Chen; Peter Hieber; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2022)
In this study, we use advance tax rulings (ATR) to investigate the impact of fee-based tax certainty on risky investment decisions of a firm under both cash flow and tax uncertainty. We model and analyze the multi-dimensional nature of tax uncertainty from tax reforms and tax audits in expected tax rates, tax bases, and in conjunction with loss offset restrictions. A tax au-thority can provide tax certainty by offering ATRs and charging an ATR fee. The fee imposes costs on firms. We determine the critical ATR fee range in which the ATR is acceptable for both the firm and tax authority. Gener-ally, we find the ATR allows the firm to take on riskier investments. If the ATR is employed in an environment with a generous tax loss offset policy, the ATR's inducement effect on risky investments is even strengthened. We identify settings in which the tax authority is willing to charge zero or even negative ATR fees. Negative fees can be interpreted as enhanced services to taxpayers that reduce taxpayers' compliance costs. Surprisingly, we find that an ATR is particularly effective for firms with low risk aversion. Our findings suggest that ATRs can effectively fight tax uncertainty and stimulate investment. However, their effectiveness crucially depends on tax system features such as loss offset restrictions and the ATR fee.
Keywords: G11; H25; M41; M42; M48; 330; advance tax ruling; cash flow uncertainty; loss offset provisions; optimal fee; optimal investment; tax uncertainty